North Sulawesi Traditional Musical Instrument Introduction Application Using Augmented Reality: Aplikasi Pengenalan Alat Musik Tradisional Sulawesi Utara Menggunakan Augmented Reality - Valentina Dhamayanti; Arie S.M.Lumenta; Brave A. Sugiarso (Jurnal Teknik Elektro dan Komputer, 2023)
Abstract —  North Sulawesi's traditional musical instruments are one of the cultures that must be maintained and preserved, especially by the younger generation. Traditional culture is slowly being replaced by modern culture. Cultural arts lessons in schools are mostly only through books. Students rarely see and hear North Sulawesi musical instruments directly, usually because traditional musical instruments are not socialized at school. Therefore, to make it easier for students at school to get to know North Sulawesi's traditional musical instruments, an application was created that uses augmented reality technology, with students' smartphones as the medium. This application will display a 3D model of a musical instrument and can be played via the buttons provided. Applications are made using the MDLC (Multimedia Development Life Cycle) method which contains 6 stages, namely concept, design, material collecting, assembly, testing, and distribution. The application was tested at SD Negeri 126 Manado with 3 stages of the questionnaire where the questionnaire stages 1 and 2 were a test of ability before and after the application was introduced, and stage 3 was a satisfaction questionnaire with the application. The ability test results after the application was introduced increased from 35.2% to 90%. In addition, there is also a questionnaire containing application satisfaction where 80% of respondents answered that the application had helped them get to know North Sulawesi's traditional musical instruments.   Key words — 3D, AR Camera, Augmented Reality, Traditional Musical Instruments   Alat musik tradisional Sulawesi Utara merupakan salah satu kebudayaan yang harus kita jaga dan patut dilestarikan. Masyarakat semestinya mempunyai rasa tanggung jawab yang tinggi untuk melindungi serta melestarikan kebudayaan lokal, khususnya generasi muda. Apalagi dengan kemajuan teknologi yang sangat pesat membuat kebudayaan-kebudayaan yang berbau tradisional perlahan-lahan sirna dan digantikan oleh kebudayaan modern. Berdasarkan hasil kuisioner yang berisi pertanyaan seputar alat musik tradisional Sulawesi Utara, pertanyaan yang berhasil dijawab benar adalah 35,2%. Hal ini menunjukkan minimnya pengetahuan anak-anak terhadap kebudayaan mereka sendiri. Pelajaran seni budaya di sekolah kebanyakan hanya melalui buku. Siswa jarang melihat dan mendengar alat musik Sulawesi Utara secara langsung, biasanya karna alat musik tradisional kurang disosialisasikan ke sekolah. Maka dari itu, untuk memudahkan siswa di sekolah untuk mengenal bentuk serta suara dari masing-masing alat musik tradisional Sulawesi Utara, dibuatlah aplikasi yang menggunakan teknologi augmented reality, dengan smartphone siswa sebagai medianya. Aplikasi ini akan menampilkan model 3D dari alat musik dan memberikan akses pada siswa untuk memainkan alat musik melalui tombol-tombol yang telah disediakan.